The lipid peroxidation end-product and oxidant 4-hydroxynonenal induces insulin resistance in rat slow-twitch skeletal muscle. (February 2014) - Prasannarong, Mujalin; Santos, Fernando R.; Hooshmand, Payam; Hooshmand, Paria; Giovannini, Franchesca J.; Henriksen, Erik J.
Abstract Context: The lipid peroxidation end-product and oxidant 4-hydroxynonenal (4-HNE) impairs cell function. However, the impact of 4-HNE on the glucose transport system in mammalian slow-twitch skeletal muscle is not known. Objective: We assessed the effects of 4-HNE on insulin signalling and glucose transport activity in slow-twitch muscle by incubating soleus strips from lean Zucker rats with 4-HNE (50 µM) in the absence or presence of insulin (5 mU/ml) for up to 6 hr. Results: Insulin-stimulated glucose transport activity was significantly (p < 0.05) decreased by 4-HNE at 2 hr. AS160 Thr642 phosphorylation was decreased at 2 hr, whereas Akt Ser473 phosphorylation and IRS-1 protein expression were not substantially changed until 4 hr. IRS-2 protein expression was slightly decreased only at 6 hr. Conclusions: The lipid peroxidation end-product and oxidant 4-HNE induces insulin resistance of glucose transport activity in rat slow-twitch skeletal muscle, initially associated with impaired phosphorylation of AS160.